PENGARUH VARIASI KONSENTRASI GELLING AGENT HPMC (Hidroxypropyl methylcellulose) TERHADAP SIFAT FISIK GEL EKSTRAK ETANOL BIJI EDAMAME (Glycine max) - Dewi Rashati, Icha Ayuning Suprayitno (AKADEMI FARMASI JEMBER, 2019)
Edamame seeds (glycine max (L) merr) is a soybean variety that is harvested while still young. Isoflavones present in soybeans such as deidzein, glycitein, and genistein have activity in inhibiting the tyrosinase enzyme to achieve skin lightening effects for skin whitening cosmetics. In this study the gel was formulated with HPMC (Hydroxypropyl methylcellulose) 2%, 3%, 5% as a gel forming agent. Evaluation includes organoleptic, homogeneity, pH, viscosity, and spreadability. The results of organoleptic evaluation of gel form in formula 1 fulfill the requirements, in formula 2 and 3 do not meet the requirements. The physical properties of the odor and color organoleptic formulas 1, 2, and 3 are eligible. in the homogeneity test of formulas 1, 2, and 3 are homogen. In the pH test formula 1,2,3 fulfills skin pH susceptibility pH 6. In the viscosity test of formula 1 250 dPa.S, Formula 2 500 dPa.S and formula 3 800 dPa.S.in the spread test of formula 1 it is 4.4cm, formula 2 is 3.8cm, and formula 3 is 3.7cm. From the results test of the Formula 1 (2% HPMC) meets all physical requirements of the gels.Keywords :Gel, HPMC, Sifat Fisik Edamame